Circulation microRNA expression profiles in patients with complete responses to chemoradiotherapy in nasopharyngeal carcinoma - Wardana, Tirta; Chasanah, Siti Nur; Oktriani, Risky; Herawati, Cita; Anwar, Sumadi Lukman; Astuti, Indwiani; Haryana, Sofia Mubarika (KeAi Communications Co., 2022)
Background: Nasopharyngeal carcinoma (NPC) is endemic cancer in Southeast Asia with a relatively poor prognosis. Chemoradiotherapy is a primary treatment that advantages certain patients, particularly in the early stages. New predictive and prognostic biomarkers are required to guide and select the best treatment. Aims: To evaluate the circulation expression profile of microRNAs (miRNAs) associated with responses to chemoradiotherapy in nasopharyngeal carcinoma. Methods: Peripheral blood from 17 patients was collected before and after chemotherapy and radiotherapy. Differential expression circulating miRNAs were analyzed using microRNA Cancer Panels and were compared among patients with complete responses. Differential expression analysis using GenEx 7 Multid, statistic represented by GraphPad Prism 9. Alterations mechanism signaling pathways and biological function using IPA (Ingenuity Pathways Analysis). Results: Using microRNAs Cancer Plate consisting of 116 miRNAs, we identified ten circulating miRNAs that were differentially expressed in NPC patients after chemoradiotherapy. Unsupervised clustering and confirmation using qRT-PCR showed that miR-483-5p, miR-584-5p, miR-122-5p, miR-7-5p, miR-150-5p were overexpressed and miRNA are miR-421, miR-133a-3p, miR-18a-5p, miR-106b-3p, miR-339-5p were significantly downregulated after chemoradiotherapy (p < 0.0001). In addition, ROC analysis through AUC (Area Under Curve) with 99% confidence interval (CI) p value < 0.0001. Gene enrichment analysis of microRNAs and the targeted proteins revealed that the main involved pathways for chemoradiotherapy in NPC were cell death and survival signaling pathways. Conclusion: qPCR profiling in circulating blood compared before and after chemoradiotherapy in nasopharyngeal carcinoma can identify pathways involved in treatment responses. miR-483-5p, miR-584-5p, miR-122-5p, miR-7-5p, miR-150-5p, miR-421, miR-133a-3p, miR-18a-5p, miR-106b-3p, miR-339-5p are differentially regulated after chemoradiotherapy in NPC.